Fully 3D Printed Tin Selenide (SnSe) Thermoelectric Generators with Alternating n-Type and p-Type Legs - Geraint Howells (ACS Applied Energy Materials, 2023)
Tin selenide (SnSe) has attracted much attention in the field of thermoelectrics since the discovery of the record figure of merit (zT) of 2.6 ± 0.3. While there have been many publications on p-type SnSe, to manufacture efficient SnSe thermoelectric generators, ann-type is also required. Publications on n-type SnSe, however, are limited. This paper reports a pseudo-3D-printing technique to fabricate bulk n-type SnSe elements, by utilizing Bi as a dopant. Various Bi doping levels are investigated and characterized over a wide range of temperatures and through multiple thermal cycles. Stable n-type SnSe elements are then combined with printed p-type SnSe elements to fabricate a fully printed alternating n- and p-type thermoelectric generator, which is shown to produce 145 μW at 774 K.